1999
DOI: 10.1210/jcem.84.2.5467
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Effects of Slow-Release Lanreotide, a Slow-Release Somatostatin Analog, in Acromegalic Patients1

Abstract: Cardiac involvement, mostly characterized by left ventricular hypertrophy associated with various degrees of cardiac dysfunction, greatly contributes to the increased mortality and morbidity observed in acromegaly. Lanreotide is a new SRIF analog characterized by a slow-release (SR) formulation with the peculiarity of a 30-mg im administration every 10-14 days. In this study, 13 patients with postoperative active acromegaly (9 females, 4 males, 45.9 +/- 16.3 yr old) underwent an echo-Doppler and hormonal study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…402 The specificity of heart disease in acromegaly is also supported by the evidence that pharmacological suppression of GH production leads to significant regression of hypertrophy and improvement of cardiac dysfunction. 385,403,404 Several studies have demonstrated that LV hypertrophy can be reversed by suppression of GH and IGF-1 levels with surgical treatment for acromegaly or with administration of octreotide. 385,403,404 The increased prevalence of LV hypertrophy in patients with hypertension and glucose tolerance abnormalities emphasizes the need for optimal control of blood pressure and hyperglycemia together with efficacious suppression of GH and IGF-1 levels.…”
Section: 394mentioning
confidence: 99%
See 1 more Smart Citation
“…402 The specificity of heart disease in acromegaly is also supported by the evidence that pharmacological suppression of GH production leads to significant regression of hypertrophy and improvement of cardiac dysfunction. 385,403,404 Several studies have demonstrated that LV hypertrophy can be reversed by suppression of GH and IGF-1 levels with surgical treatment for acromegaly or with administration of octreotide. 385,403,404 The increased prevalence of LV hypertrophy in patients with hypertension and glucose tolerance abnormalities emphasizes the need for optimal control of blood pressure and hyperglycemia together with efficacious suppression of GH and IGF-1 levels.…”
Section: 394mentioning
confidence: 99%
“…385,403,404 Several studies have demonstrated that LV hypertrophy can be reversed by suppression of GH and IGF-1 levels with surgical treatment for acromegaly or with administration of octreotide. 385,403,404 The increased prevalence of LV hypertrophy in patients with hypertension and glucose tolerance abnormalities emphasizes the need for optimal control of blood pressure and hyperglycemia together with efficacious suppression of GH and IGF-1 levels. 401 Although a case report of severe congestive HF from acromegalic cardiomyopathy suggests that cardiac function could be recovered significantly and that LV mass could be decreased with transsphenoidal surgery and administration of octreotide, 405 other reports suggest that these beneficial effects appear earlier in young patients with short disease duration than in elderly patients.…”
Section: 394mentioning
confidence: 99%
“…Octreotide and lanreotide have also been shown to decrease left ventricular mass [68, 69, 70, 71, 72]and to improve diastolic function [68, 69, 70, 71, 72]. An improvement in systolic function was demonstrated in patients with overt heart failure [73]and in patients without symptoms of cardiac disease after 1 year of treatment with octreotide if they achieved disease control [74].…”
Section: Gh-secreting Pituitary Adenomasmentioning
confidence: 99%
“…However individual responses of acromegalic patients to somatostatin analogs are very variable. At least 25-30% of treated patients did not show improvement in terms of LV hypertrophy [81,84]. It should be noted that the cardiac effects of somatostatin analogs appear to be related not only to the strict control of acromegaly but also to patients' age as well as duration of GH and IGF-I hypersecretion before intervention [84,86].…”
Section: Effects Of Gh-lowering Treatments On Heartmentioning
confidence: 99%
“…Additional changes include amino acid substitutions within binding site 1 and a further modification by the addition of polyethylene glycol moieties that increase the half-life and reduce the immunogenicity of the molecule [94]. Improvement of cardiac hypertrophy and performance has also been reported after treatment with long-lasting formulations of somatostatin analogs such as octreotide-LAR or lanreotide [84,85]. However individual responses of acromegalic patients to somatostatin analogs are very variable.…”
Section: Effects Of Gh-lowering Treatments On Heartmentioning
confidence: 99%